The Effect of Safety Training and Technology on Ship Officers Performance and Its Implications on Human Resource Competency on Dynamic Positioning 2 Ship at PT Wintermar Offshore Marine Indonesia - Arifianto Arofah Inada; Damoyanto Purba; Didik Sulistyo Kurniawan; Bambang Sumali (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
This research aims to analyze the influence of training and safety technology on the performance of ship officers and its implications for human resource (HR) competence on the Dynamic Positioning 2 (DP2) vessel at PT Wintermar Offshore Marine Indonesia. The issues raised include significant investments in training, the use of outdated DP2 technology, and challenges in implementing training and compliance with safety procedures. The population of the study consists of ship crew members on board in 2024, with a sample of 80 Dynamic Positioning Officers (DPOs). The research method employs a quantitative approach, using questionnaires for data collection, and analysis is conducted using SMART PLS. The results indicate that training and safety technology significantly influence the performance of ship officers, positively impacting HR competence. The dimension that best reflects training is the relevance of the material, while for safety technology, the IoT system has a dominant influence. Based on the findings, it is recommended that the company adopt innovative approaches to problem-solving and update the satellite communications system to support field operations.